Biomimetic synthesis of cyclic peptides using novel thioester surrogates - Hemu, Xinya (2016)
Acyl shifts involving N-S and S-S rearrangements are reactions central to the breaking of a peptide bond and forming of thioester intermediates in an intein-catalyzed protein splicing that ultimately leads to the formation of a new peptide bond by an uncatalyzed S-N acyl shift reaction. To mimic these three acyl shift reactions in forming thioesters and the subsequent peptide ligation, here we describe the development of two 9-fluorenylmethoxycarbonyl (Fmoc)-compatible thioester surrogates that can undergo uncatalyzed N-S, S-S, and S-N acyl shifts for preparing thioesters and cyclic peptides. These surrogates were incorporated as a C-terminal amido moiety of a target peptide using Fmoc chemistry by solid-phase synthesis, and then transformed into a thioester or thiolactones via two acyl shift reactions with or without the presence of an external thiol under acidic conditions. The proposed intein-mimetic thioester surrogates were prepared using readily available starting materials including N-methyl cysteine or 2-thioethylbutylamide. A key functional moiety shared in their design is the thioethylamido (TEA) moiety, which is essential to effect a proximity-driven N-S acyl shift under a favorable five-member ring transition in the breaking of a peptide bond. Thus, the tandem series of acyl shifts effected by a TEA moiety in a thioester surrogate together with a thioethylamino moiety of an N-terminal Cys residue in a linear peptide precursor are chemical mimics of an intein, as they mediate both excision and ligation reactions in forming cyclic peptides including cyclic conotoxin and sunflower trypsin inhibitor described herein.